2006
DOI: 10.1002/app.23900
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization behavior of nylon 11/montmorillonite nanocomposites under annealing

Abstract: Exfoliated nylon 11/montmorillonite (MMT) nanocomposites were prepared via in situ polymerization by the dispersion of organically modified MMT in 11-aminoundecanoic acid monomer. The polymorphic behavior of the nylon 11/MMT nanocomposites was investigated with X-ray diffraction, transmission electron microscopy, and Fourier transform infrared with attenuated total reflectance. MMT induced and stabilized the d-crystalline form of nylon 11. The crystal structure of nylon 11 was transformed from a hexagonal d-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Second, one can envisage that, as for PA6, there are strong interactions between the clays surfaces and the PA11 chains which favor the formation of the α form rather than the γ one. Particularly, Zhang et al have shown that the hydrogen bonds of PA11 are weakened upon addition of clay that restricts the formation of hydrogen bonding sheets by forcing the amide groups out of the hydrogen bonding sheets 51. Moreover, VanDerHart et al have shown by means of RMN experiments that, the γ‐phase growth from the clay surface, obtains a head start on any growth of the α‐phase originating in regions away from the clay surface 52.…”
Section: Resultsmentioning
confidence: 99%
“…Second, one can envisage that, as for PA6, there are strong interactions between the clays surfaces and the PA11 chains which favor the formation of the α form rather than the γ one. Particularly, Zhang et al have shown that the hydrogen bonds of PA11 are weakened upon addition of clay that restricts the formation of hydrogen bonding sheets by forcing the amide groups out of the hydrogen bonding sheets 51. Moreover, VanDerHart et al have shown by means of RMN experiments that, the γ‐phase growth from the clay surface, obtains a head start on any growth of the α‐phase originating in regions away from the clay surface 52.…”
Section: Resultsmentioning
confidence: 99%
“…Neat PA11 sample exhibits three characteristic peaks at diffraction angles of around 2θ = 7.23°, 20.23° and 23°, respectively associated to the (001), (100) and (010/110) plane, indicating the presence of the triclinic α-form of nylon 11 [6,29,30]. Unlike layered clays, whose primary diffraction peaks shift significantly to higher/lower angles when it is aggregated/exfoliated in a polymer matrix [31], the unit layer in a single rod crystal cannot be separated or delaminated, because this would imply the disruption of the silicate structure. Therefore, the characteristic diffraction peak of the PLG nanofiller, located at 2θ = 8.4°, keeps its original position even if the PLG is well dispersed in the matrix [12,18,32].…”
Section: Morphological and Structural Properties Of Pa11 Nanocompositesmentioning
confidence: 99%
“…Zhang et al [120] have observed that the addition of MMT induced a change in the crystalline form of Nylon 11, from the pseudohexagonal δ ′ form to the more stable hexagonal δ form. This was attributed to the restricted formation of hydrogen -bond sheets, forcing the amide groups of nylon out of the hydrogenbond sheets in the presence of MMT.…”
Section: Nylon 11mentioning
confidence: 99%